Effect of Sampling Errors on Single Sampling Plan Rectifying Inspection - Braimah, O. J.; Jaiyeola, S. B.; Rabiu, M.; Ibrahim, S. A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
Quality  control  systems  can  be  divided  into  process  control  and  product  control. Inspection plans play a vital role in product control and must be used wisely.  Recently, researchers in various quality control procedures consider the possibility of inspection errors as an important issue.  To assess the performance of Single Sampling Plan, Average Outgoing Quality (AOQ) and , Average Total Inspection (ATI) are used. The impacts of inspection error for varying producer’s and consumer’s risk are examined using AOQ and ATI to assess the performance. A statistical software R (R-package) was used to obtain the two parameters and their plots at varying producer’s and consumer’s risk points. From the analyses, increase in both producer’s and consumer’s risks (α, β) resulted in reduced AOQ for p < 0.06. Between p = 0.07 and p = 0.08, there was no pattern. However, when p > 0.09, as α and β increase, AOQ also increases.